The Influence of Promotion and Service Quality on Consumer Purchase Decisions - Tanty Sondari; Budhie Satriawan; Dea Afriliani (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The development of the business world is experiencing very rapid growth; this has an impact on business actors who have to keep up with the competition to get opportunities in their business fields. The number of new competitors causes consumers to have more choices of goods/services to be used. This study aims to determine the effect of Promotion and Service Quality on Consumer Purchase Decisions at Toy Stores during the Covid-19 Pandemic. The method used in this study is a quantitative method using primary and secondary data. The number of samples in the study was 72 respondents, namely customers in the Kingkong Toys Whatsapp group. Analysis of the data used in this study is using path analysis which is processed using SPSS Version 26. The results of this study indicate that the variables of promotion and service quality have a positive and significant effect on purchasing decisions.